THE FINAL FRONTIER OF CYBERSPACE: THE SEABED BEYOND NATIONAL JURISDICTION AND THE PROTECTION OF SUBMARINE CABLES. Issue 3 (July 2022) - Guilfoyle, Douglas; Paige, Tamsin Phillipa; McLaughlin, Rob
Abstract: Cyberspace is now acknowledged not only as the newest domain of warfare, but also as a space vital to economic, educational and cultural development for all States. This thin consensus ignores the fundamental fact that the backbone of cyber infrastructure—submarine telecommunication cables—is not (for the large part) located within sovereign territorial jurisdiction. The radically increased reliance of States upon submarine data cables emphasises their vulnerability to damage by malicious acts, accidents, or natural phenomena. Faced with these problems, legal analysis has tended to identify gaps or deficiencies in the law, and propose the creation of new legal instruments. The contribution of this article is twofold. First, it expands the frame of analysis to include deliberate damage to cables not only in peacetime but under the law of armed conflict. Second, rather than treating the legal framework as inherently deficient, it considers the extent to which existing rules and principles can be progressively developed, interpreted, or creatively applied to close perceived gaps. This article surveys the existing law specific to the protection of submarine cables and assesses how general principles of the law of the sea, State responsibility, the law on the use of force, and the law of armed conflict apply to this problem. It thus considers in turn the applicable 'law of peace', the jus ad bellum and the jus in bello .